2017
DOI: 10.1111/conl.12398
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovering the Potential of Indigenous Storytelling for Conservation Practice

Abstract: Several intergovernmental policy instruments, including the World Heritage Convention of UNESCO and the Convention on Biological Diversity, have proposed to develop integrated strategies to build bridges between biological and cultural diversity agendas. We contend that to succeed in this endeavor, it is crucial to link biocultural revitalization to conservation practice. Our hope with this review is to call attention to indigenous storytelling as an option worth adding to the repertoire of conservation practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(129 citation statements)
references
References 44 publications
1
125
1
2
Order By: Relevance
“…We encouraged the participants to tell their own stories through different type of art forms. Our observations regarding the value of art for doing this supports the findings of Fernández-Llamazares and Cabeza [24] that storytelling can be a powerful vector for identifying key threats to native maize biocultural conservation, as well as for promoting knowledge transfer and reducing the distance between generations. In addition, we observed that discussing community memories related to native maize during the focus group discussions helped create an atmosphere of equity among participants from different social and educational levels in the community, since they all shared the same historical background and were facing the same problems.…”
Section: Lessons Learned From Using Creativevoicesupporting
confidence: 85%
See 2 more Smart Citations
“…We encouraged the participants to tell their own stories through different type of art forms. Our observations regarding the value of art for doing this supports the findings of Fernández-Llamazares and Cabeza [24] that storytelling can be a powerful vector for identifying key threats to native maize biocultural conservation, as well as for promoting knowledge transfer and reducing the distance between generations. In addition, we observed that discussing community memories related to native maize during the focus group discussions helped create an atmosphere of equity among participants from different social and educational levels in the community, since they all shared the same historical background and were facing the same problems.…”
Section: Lessons Learned From Using Creativevoicesupporting
confidence: 85%
“…Photovoice has received increased uptake in recent years and has been used as a method in the fields of public health [18][19][20] psychology [21], education [22], and social science [23]. It has also been implemented to a lesser extent, although with positive outcomes, in community-based environmental and indigenous studies research [17,24]. For example, Thompson [25] found in Photovoice a useful way to raise the voices of young farmers from Sierra Leone on their needs and relationship to the environment after civil war.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key factors was developing methods to restore intergenerational connectivity, and how the research itself can be a method for decolonizing transmission pathways. Previous research observes challenges related to disruption of Indigenous knowledge transmission brought on by colonial impacts on economic and education systems (McCarter et al, 2014b;Tang & Gavin, 2016), and alternately the potential for biodiversity conservation through strengthening intergenerational communication (Fernández-Llamazares & Cabeza, 2018). By searching out ways of strengthening intergenerational knowledge transmission in the research process itself, we redefined and centered youth and community knowledge keepers as the researchers and experts.…”
Section: Reciprocity: Ensuring Benefit To Communitymentioning
confidence: 99%
“…Here, we present the results in the form of three scenarios of harvesting practices witnessed by the lead author while living in Cumberland House and participating in activities with the residents. This presentation is in keeping with the style used by community members to share their Indigenous knowledge through storytelling and is just beginning to be taken up in scientific practice (Fernández‐Llamazares and Cabeze ).…”
Section: Resultsmentioning
confidence: 89%